Detecting a potential causal relationship between plasma metabolites and myocardial infarction using bidirectional and two-step Mendelian randomization - Mengqi Yang; Meng Wang; Jie Li; Min Li; Xuejiao Liu; Yan Li; Yitao Xue (Scientific Reports)
Abstract Some studies have shown that plasma metabolites may be associated with myocardial infarction (MI); however, the causal relationship between plasma metabolites and MI, as well as the potential mediating role of immune cells, remains unclear. This Mendelian randomisation (MR) study utilised large-scale genome-wide association study (GWAS) summary data encompassing 1400 plasma metabolites (n = 8299), 731 immune cell traits from the GWAS Catalog consortium (n = 3757), and MI cases and controls from the FinnGen consortium (cases: n = 26,060; controls: n = 343,079). Using bidirectional MR analysis, we assessed the causal links between plasma metabolites and MI, and between immune cells and MI, excluding reverse causality. Five MR methods were applied, with inverse variance weighting used as the primary analytical approach. In addition, we conducted two-step MR to identify potential immune cell mediators. We identified 44 positive and 33 negative causal associations between genetic liability to plasma metabolites and MI. Of these, only the association between 3β-hydroxy-5-cholestenoate (OR = 0.909; 95% CI 0.871–0.950; P = 1.84 × 10–5) and MI remained statistically significant after Bonferroni correction. Additionally, eight positive and five negative causal associations were observed between immune cells and MI. Among them, HLA-DR on dendritic cells (OR = 1.039; 95% CI 1.020–1.057; P = 2.84 × 10–5) and HLA-DR on plasmacytoid dendritic cells (OR = 1.031; 95% CI 1.016–1.047; P = 4.33 × 10–5) were identified as risk factors for MI after correction. Notably, bidirectional MR revealed that the glutamine conjugate of C6H10O2 (1) (OR = 1.125; 95% CI 1.042–1.215; P = 0.003) was causally associated with increased MI risk, with no evidence of reverse causality or heterogeneity. In the two-step MR analysis, positive associations were found between this metabolite and HLA-DR on CD33-HLA-DR + cells (OR = 1.302; 95% CI 1.014–1.671; P = 0.038), and between the immune trait HLA-DR on CD33-HLA-DR + (OR = 1.035; 95% CI 1.010–1.060; P = 0.005) and MI. Furthermore, mediation analysis indicated that 7.68% of the effect of the metabolite on MI was mediated through HLA-DR on CD33-HLA-DR+. Plasma metabolites and immune cells demonstrated causal associations with myocardial infarction. Moreover, immune cells acted as mediators in the causal pathway from plasma metabolites to myocardial infarction.